Dermatologic toxicities of chemotherapy: an educational intervention for skin of color women with breast cancer. Issue 1 (30th January 2023) - Ahmad, Maham; Saeed, Sabrina; Olamiju, Brianna; Silber, Andrea; Leventhal, Jonathan
Abstract : Background: Minority patients are more likely to require dose adjustments for chemotherapy, with cultural barriers and access to medical care cited as contributory factors. Objective: We sought to pilot an educational intervention, in the form of a pamphlet, to evaluate the effectiveness of this tool in teaching skin of color (SoC) patients about potential dermatologic toxicities of chemotherapy that are relevant to their skin type. Methods: At a chemotherapy infusion center, SoC patients ( n = 26) who were receiving chemotherapy for breast cancer voluntarily consented to read an educational pamphlet and complete a series of survey questions before and after this educational intervention. Results: Most participants identified as female (96%), African American/Black (81%), and non-Hispanic (85%); all respondents had obtained at least a high school degree. Survey responses revealed a significant increase in knowledge about the potential dermatologic effects of cancer treatment after this intervention. Notably, 100% of participants either agreed or strongly agreed that they would like to see other doctors use this educational tool as a form of patient education, that they would recommend this pamphlet to other patients who are starting cancer treatment, and that the pamphlet was easy to understand. Limitations: Limitations of this study include small sample size and single-institution recruitment, which may limit generalizability. Furthermore, this study only included patients who are proficient in English. Conclusion: This study pilots an effective educational tool that addresses dermatologic toxicities of chemotherapy that are relevant to SoC patients. Further multi-institutional studies with larger sample sizes and translation to other languages can overcome the limitations of this pilot study.